Cost-utility and budget impact analyses of gefitinib in second-line treatment for advanced non-small cell lung cancer from Thai payer perspective - Thongprasert,S. (Wiley-Blackwell, 2015)
Aim: To evaluate the cost utility and budget impact of second-line gefitinib for non-small cell lung cancer from a Thai payer perspective. Methods: A Markov model with three health states (pre-progression, post-progression and death) was constructed to estimate direct medical costs and outcomes comparing four treatment options, i.e., gefitinib, erlotinib, pemetrexed and docetaxel. The model followed patients for 2years with discount rate of 3% annually. Clinical inputs and patients' characteristics were based on a randomized phase III trial (INTEREST). Costs were based on reference prices published by the Ministry of Public Health, Thailand, and other information related to treatment from expert opinion and presented in 2010. Deterministic and probabilistic sensitivity analyses were performed to determine the impact of model parameters on results. Results: In the base case model, gefitinib and erlotinib yielded equal quality-adjusted life years (QALY) but 0.0140 and 0.0110 more QALY compared with docetaxel and pemetrexed, respectively. Total costs were 188848 Baht (US$6237) for gefitinib, 196313 Baht (US$6483) for docetaxel, 249177 Baht (US$8229) for erlotinib and 275303 Baht (US$9092) for pemetrexed. Drug acquisition contributed the greatest component. A series of sensitivity analyses demonstrated the robustness to various parameter variations except for docetaxel cost and duration of treatment. The budget impact analyses demonstrate the greater the percentage of substitution of gefitinib for docetaxel (ranging from 10-60%) the greater the cost saving. Conclusion: Gefitinib is a dominant cost saving strategy compared with docetaxel for the second-line treatment of advanced NSCLC from the Thai payer perspective. © 2012 Blackwell Publishing Asia Pty Ltd.